Mekanisme Governance Dan Pengungkapan Sustainable Finance:Untuk Melihat Tingkat Kesiapan Penerapan Sustainable Finance Pada Perusahaan Jasa Keuangan Terdaftar Di BEI - Salis Musta Ani; Hotman Fredy (Jurnal Akuntansi, 2017)
This research is motivated by the lack of literature on the disclosure of sustainable finance and the need on preparing for the financial services industry in Indonesia to start implementing sustainable finance. In addition, the background of this research is the absence of standard setting of sustainable finance reporting standards, whereas the implementation of sustainable finance reporting is planned by OJK in 2016. This research is examination ofÂ  influence of governance mechanism towards sustainable finance. Data is traced from financial services companies listed on the BEI. The research method used is multiple linear regression. The result proves that size of both company and the directors affect the disclosure of sustainable finance. This study also illustrates that the average of companies in Indonesia nowadays, when using measurement items based on International Finance Corporation (IFC), report components in sustainable finance is 0.35 on average. OJK needs to pay attention to this to provide more intensive guidelines for implementation and reporting of sustainable finance.